Advanced Virtual Support for Operational Forces: A 3-Year Summary. Issue 5 (22nd October 2021) - McLeroy, Robert D; Kile, Michael T; Yourk, Daniel; Hipp, Sean; Pamplin, Jeremy C
ABSTRACT: Introduction: The Military Health System mission is to provide medical care throughout the globe to service members and beneficiaries. To achieve this mission in the most austere of locations, telemedical support is an essential force multiplier when robust in-person medical support is not feasible. This led to the development of a telemedical solution initially known as the Virtual Critical Care Consultation service which provided tele-critical care assistance to downrange providers. The VC3 system then expanded to include multiple medical specialties available for consultation. The current version of this telemedical solution is the ADvanced VIrtual Support for OpeRational Forces (ADVISOR) program which is a synchronous and asynchronous telemedicine system that was developed to provide 24/7 remote expert support to military clinicians engaged in casualty care in austere and operational environments. Materials and Methods: This manuscript reviews the ADVISOR program data collected from 2017 to 2020 and provides a rough order of magnitude for return on investment. We reviewed data collected by Operational Virtual Health Reports and Operational Virtual Health Evaluations following synchronous consultations. Part of the data reviewed was available patient demographic data, local caregiver information, the purpose of the consult, recommendations made during the consult, the technology used during the consult, and the patient disposition. They also recorded the evacuation plan for the patient and whether a medical evacuation was escalated (e.g. changed from routine to urgent, or from urgent to critical care air transport), downgraded (e.g. urgent to routine), or avoided altogether based on the telephonic consultation. Results: There were a total of 156 real-world calls during the evaluation period. The total cost savings for these calls was 1, 097, 027 (3-year program costs of 909, 973 less an average of 87, 261+/- 28, 633 per call or 2, 007, 000 total) from downgrading or avoidance of planned evacuations. The unmeasured value associated with ADVISOR consultations should also be commented on. For example, when evacuation plans are escalated based on remote expert consultation, it is probable that the escalation increases patient safety and may avoid medical complications that would result in longer term medical costs to the government. Conclusions: Based on the collected information, the financial return on investment has exceeded costs and the system is perceived as being valued added for both local caregivers and remote experts. The system appears to help optimize evacuation planning, specifically by downgrading or eliminating unnecessary evacuations.